Elevated Troponin and Jarisch-Herxheimer Reaction in Tick-Borne Relapsing Fever: A Case Report. (9th October 2011) - Hoekstra, Kenneth A.; Kelly, Michael T.
Abstract : We describe a patient with fever and borreliosis in the Northwestern Washington State, USA. The patient exhibited a classic Jarisch-Herxheimer reaction of tachycardia, hypotension, and thrombocytopenia following antimicrobial therapy, and she also developed an elevated serum cardiac troponin during therapy.